Atmospheric dry nitrogen deposition and its relationship with local land use in a high nitrogen deposition region. (15th April 2019) - Deng, Ouping; Zhang, Shirong; Deng, Liangji; Lan, Ting; Luo, Ling; Gao, Xuesong; Zhou, Wei
Abstract: Atmospheric dry nitrogen (N) deposition is a key process in the N cycle of the earth, and the land-use type might profoundly affect N deposition. However, little is known about the relationship between local land-use types and dry N deposition in an urban-rural region. Therefore, this study observed atmospheric dry N deposition in continuous 24 months (from January 2015 to December 2016) and then applied space influence area analysis to explore the multi-scale relationship between land use types and dry N deposition. The results showed that the key land use areas in the range of 4 km of monitoring point were closely related to dry N deposition flux. The spatial and temporal variation of atmospheric dry N deposition was explained by "source" and "sink" land use types. For "source" land use type, agro-facility area contributed to dry NH4 ⁺-N deposition, while dry NO3 − -N and dry organic N deposition was attributed to urban and high way areas. On the other hand, agricultural land with suitable and limited fertilizer application, country road without hardening and forests were considered as the "sink" for N deposition. These "sink" land use types should be considered actively in urban and rural planning. Graphical abstract: Multiscale Influence districts extracting of a monitoring site (a) and pearson correlation between annual dry N deposition flux and land use area in multiscale Influence districts (b).Image 1 Highlights: Land use type within 4 km is most critical for atmospheric dry N deposition. Dry NH4 ⁺ -N, DNO3 - -N and DrON deposition were affected by varied "Source" land use type. Agricultural land with suitable fertilizer application, unpaved country road and forest were the "sink" for N deposition.